Effect of a Monascus sp. Red Yeast Rice Extract on Germination of Bacterial Spores - Husakova, Marketa; Plechata, Michaela; Branska, Barbora; Patakova, Petra (Frontiers in Microbiology, 2021)
The pink-red color of traditional sausages (cured meat) is the result of nitrite addition and the formation of nitrosomyoglobin. However, the pleasant color of processed meat products is a side effect of nitrite addition while the main anticipated goal is to suppress the germination of clostridial spores. The fungus Monascus is known as a producer of oligoketide pigments, which are used in Asian countries, especially in China, for coloring foods, including meat products. Although, different biological activities of Monascus pigments have been tested and confirmed in many studies, their effect on germination of bacterial spores has never been investigated. This study is focused on testing the activity of red yeast rice (RYR) extract, containing monascin, rubropunctatin, rubropunctamine complexes and monascuspiloin as the main pigments, on germination of Clostridium and Bacillus spores. It was found that addition of nitrite alone, at the permitted concentration, had no effect on spore germination. However, the combined effects of nitrite with NaCl, tested after addition of pickling salt, was efficient in inhibiting the germination of C. beijerinckii spores but had no effect on B. subtilis spores. In contrast, total suppression of C. beijerinckii spore germination was reached after addition of RYR extract to the medium at a concentration of 2% v/v. For B. subtilis, total inhibition of spore germination was observed only after addition of 4% v/v RYR extract to the medium containing 1.3% w/w NaCl.